DETERMINAN PRODUKSI IKAN TANGKAP DI KOTA SIBOLGA - Rita Herawaty Br Bangun (JURNAL AGRICA, 2018)
This study aims to see the condition of capture fisheries and to know the factors that affect the production of capture fisheries in the city of Sibolga. The method used in this study is Multiple Regression Analysis. The results of this study indicate that the number of fishermen, the number of fishing boats, the number of fishing equipment, the number of fish landing bases, the number of fish drying industries simultaneously significantly affect the production of catch fish while partially only the number of fish landing bases affecting the production of catch fish in City of Sibolga.Keywords: production of capture fishery, Multiple Regression Analysis